Multisensory Technology for Flavor Augmentation: A Mini Review - Velasco, Carlos; Obrist, Marianna; Petit, Olivia; Spence, Charles (Frontiers in Psychology, 2018)
There is growing interest in the development of new technologies that capitalize on our emerging understanding of the multisensory influences on flavor perception in order to enhance human-food interaction design. This review focuses on the role of (extrinsic) visual, auditory, and haptic/tactile elements in modulating flavor perception and more generally, our food and drink experiences. We review some of the most exciting examples of recent multisensory technologies for augmenting such experiences. Here, we discuss applications for these technologies, for example, in the field of food experience design, in the support of healthy eating, and in the rapidly-growing world of sensory marketing. However, as the review makes clear, while there are many opportunities for novel human-food interaction design, there are also a number of challenges that will need to be tackled before new technologies can be meaningfully integrated into our everyday food and drink experiences.